(untitled) (Teras, 2023)
Dead-end Road – Gombong Km. 07 Banyumas is a district road that has changed its function to become a provincial road. The road has heavy traffic and the vehicles passing through it are heavily loaded, so the road suffers a lot of damage.According to the PCI method, it shows that with the area of ​​Jalan Dead End – Gombong Km. 07 Banyumas 21,000 m2 there is damage of 2299.2 m2 or 11.00%. and roadworthiness level of 46.23%. These results state that the value is still in the moderate condition value (Fair).According to the Binamarga method, the results for the evaluation results of the road damage assessment obtained a damage value of 19, included in the road condition value of 7, and based on the order of priority, entered in priority order 4, which means that the road condition is still bad, a Periodic Maintenance Program must be carried out.Based on the level of damage according to the PCI method which is in the moderate category (fair) and the level of damage according to Binamarga is in the moderate category or the Periodic Maintenance Program, a decision was made to improve the road seen from several segments/areas that experienced very bad damage so that the comfort of road users was disturbed and could resulted in a traffic accident, therefore a re-planning program was carried out with the results of the layer thickness. AC-WC = 40 mm AC-BC = 60 mm AC-Base = 80 mm LPA Class A = 300 mm Keywords: Road Damage, PCI (Pavement Condition Index) Binamrga.